2014
DOI: 10.5835/jecm.omu.31.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Demographic data of 112 cases transported to the emergency medicine clinic

Abstract: Article HistoryReceived 01 / 04 / 2014 Accepted 11 / 06 / 2014The coordination between pre-hospital emergency health service and emergency department is one of the major indicators of the quality of emergency services. This coordination heavily depends on the appropriate patient referrals made by 112 command and control centers. The aim of this study is to examine the collaboration and coordination between emergency departments and 112 Command and Control Center in such regions where there are more than one ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Looking to the distribution of presentations by days, the most common presentation was made on Saturday. Similar studies have reported more presentation at weekends (3,8,(12)(13). As specified in the literature, presentation to EDs increases at weekends since outpatient clinics are closed.…”
Section: Chartsupporting
confidence: 79%
See 1 more Smart Citation
“…Looking to the distribution of presentations by days, the most common presentation was made on Saturday. Similar studies have reported more presentation at weekends (3,8,(12)(13). As specified in the literature, presentation to EDs increases at weekends since outpatient clinics are closed.…”
Section: Chartsupporting
confidence: 79%
“…According to the data by "Ministry of Health" trauma emergencies (25.7%) and cardiovascular system emergencies (19.5%) take place in the first two ranks among the preliminary diagnosis of emergencies nationwide (16). Studies conducted at different times, in different regions, and different lines of hospitals have reported the most common admission diagnosis in patients brought to EDs with 112 as trauma emergencies (3,4,12,17). Similarly to the literature, the most common cause was trauma emergency in our study.…”
Section: Chartmentioning
confidence: 99%